VRIO Analysis in Developing Branding Strategies for Egg-Based Food Products as Souvenirs from Blitar: Local Perspective - Utama, Adiguna Sasama Wahyu; Wardani, Shanti Ike; Putra, Aditya Wirawantoro (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
Blitar is rich in tourism potential. The local economy stands to benefit significantly from tourism, creating job opportunities and enhancing community development. Blitar's position as a major egg producer offers unique opportunities for developing egg-based souvenirs. However, challenges include identifying appealing products and effective branding strategy is required to enhance the marketability of these products, fostering economic growth and tourism in the region. This study utilizes a mixed-method approach to explore consumer perceptions of egg-based processed products in Blitar, combining quantitative surveys with qualitative interviews of business actors. A survey of 61 respondents gathered measurable data on consumer preferences and factors influencing purchasing decisions. In-depth interviews provided insights into marketing strategies and challenges faced by producers. The study employs descriptive statistics and VRIO analysis to develop effective branding strategies for promoting processed egg products as signature souvenirs from. The analysis reveals that respondents indicating higher interest in egg-based products as souvenirs from Blitar as food significantly influences their choice of tourist destinations, with a strong preference for local ingredients. However, awareness of Blitar’s egg production potential is low, leading to limited appeal for egg-based products. The VRIO analysis shows organizational weaknesses hinder competitive advantage despite valuable product features. Effective branding strategies tailored to consumer expectations are crucial for market success. Enhancing product awareness and education through organized action can further strengthen the appeal of these culinary offerings in tourism.